2019
DOI: 10.1177/0004867419837358
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting atypical antipsychotics in schizophrenia: A systematic review and meta-analyses of effects on functional outcome

Abstract: Objective: Impairment in psychosocial function is common in schizophrenia. Long-acting injectable atypical antipsychotics are thought to enhance psychosocial function by boosting adherence. However, no systematic review has examined the effects of long-acting injectable atypical antipsychotics on psychosocial function in clinical trials. Methods: We searched major databases including Medline/PubMed, PsychINFO, EMBASE, CINAHL, Scopus, Web of Science, Cochrane Central Register of Controlled Trials and Clinical T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…A literature review has demonstrated that SGA LAI have an advantageous profile of efficacy, safety, and tolerability, thus a potential for improved adherence 25,26 . LAI have also shown a beneficial impact on recovery of psychosocial function 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A literature review has demonstrated that SGA LAI have an advantageous profile of efficacy, safety, and tolerability, thus a potential for improved adherence 25,26 . LAI have also shown a beneficial impact on recovery of psychosocial function 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Having said this, other researchers have found no difference in effectiveness between the different strengths of insulin glargine and concerns with possible underdosing with the 300 IU/ml formulation [76]. These "evergreening" activities by the originator company to preserve its market share in the face of potential competition are similar to the launch of different devices for the treatment of asthma to try and improve adherence rates and protect sales as well as the development of longer-acting oral formulations and intramuscular formulations of atypical antipsychotics to improve compliance and reduce recurrences [77][78][79][80]. Such company activities are also seen in other disease areas.…”
Section: Introductionmentioning
confidence: 99%
“…Integration into work, social and leisure activities is a key concern when treating people with schizophrenia. A recent meta-analysis showed that LAIs were superior to both placebo and oral antipsychotic medications in improvements in functional outcomes, 10 thus aiding in meeting the challenge of patient integration. Survey results indicated a positive shift in patient–clinician dynamics when patients received Invega Trinza.…”
Section: Discussionmentioning
confidence: 99%